2022
DOI: 10.5860/crl.83.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Scholarly Search Skills Based on Resource and Document Selection Behavior among Researchers and Master’s Students in Engineering

Abstract: This study focuses on differences in the scholarly search approaches of researchers and students in contemporary information environments by examining use of academic resources and elements in search results (such as title or abstract) to identify scholarly search knowledge and skills. To examine how users select documents for different search situations, an online survey of resource selection and the use of search result elements was conducted among 48 researchers and 40 master's students in the field of engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Digital Reference Services: Online information resources have become the first choice of researchers when seeking information resources for their research. However, they often face challenges in using these resources (Hagiwara et al, 2022;Akande & Popoola, 2022). Librarians have found that with technology, they can extend the reference services that they traditionally render within the library to the digital space.…”
Section: Information Resource Managementmentioning
confidence: 99%
“…Digital Reference Services: Online information resources have become the first choice of researchers when seeking information resources for their research. However, they often face challenges in using these resources (Hagiwara et al, 2022;Akande & Popoola, 2022). Librarians have found that with technology, they can extend the reference services that they traditionally render within the library to the digital space.…”
Section: Information Resource Managementmentioning
confidence: 99%